Familial deep cavitating state with a glutathione metabolism defect. Issue 12 (9th November 2019) - Rendu, John; Van Noolen, Laetitia; Garrel, Catherine; Brocard, Julie; Marty, Isabelle; Corne, Christelle; Fauré, Julien; Besson, Gérard
Abstract: Adult genetic disorders causing brain lesions have been mostly described as white matter vanishing diseases. We present here the investigations realized in patients referred for psychiatric disorder with magnetic resonance imaging showing atypical basal ganglia lesions. Genetic explorations of this family revealed a new hereditary disease linked to glutathione metabolism.